MODEL SISTEM INFORMASI TERINTEGRASI FUNGSI ACCOUNT OFFICER DALAM LEMBAGA KEUANGAN MIKRO/SYARIAH - Zen Munawar; Dadad Zainal Musadad; Nia Tresniati (PROCEEDING STIMA)
Abstract On a Micro Finance Institution / Syariah there are technical problems in the field that  caused significant losses for the institutions mainly caused by the problems in lending / financing. The occurrence of credit / financing problems are generally caused by errors or irregularities at the  time of the analysis of credit / financing as the basis for a final decision for management in providing credit / financing to customers.Operational systems are built to be able to present the information systems that can meet the complete, accurate but may be a system that can detect irregularities early (early warning system) so as to prevent improper decisions. The system is built by integrating the overall presentation of information (integrated) in each work unit of the institution. And for the account officer who became a mediator for the institutions with the customer must be able to integrate the information presented is up to date in meeting the needs analysis, maintenance of quality credit / financing so that it can affect any decisions appropriately and tomake improvements on an ongoing basis. Integrated information system for account functions  financing officer for institutions with an organizational structure restricted designed to maximize the function and role of account officer in a system based on computer contained in a module that iscomplete from start to presentation of credit / financing approval package, Report the pitch-up date relating to the maintenance of the quality of credit / financing from existing customers and presenting information that was analyzed as the basis for management decision .  Keywords: Integrated information systems, credit / financing, management decisions